The Pediatrician's Dilemma: Refusing the Refusers of Infant Vaccines. Issue 3 (2015) - Block, Stan L.
Abstract : "Their decision about vaccines is based on an emotional response to the perceived risk of harm from vaccines, weighed against the intangible risk of disease they have never seen." "Vaccine refusal is often only the first step in a one-sided parent-physician relationship, where our experience, training and expertise are disregarded." A mother new to my general pediatrics practice says that she wants no vaccines for her infant because she says, "I have read on the internet…, " or "I heard from a nurse…, " or "So-and-so celebrity says they can cause autism, brain damage, poisoning, cancer, neurological disorders, and even death." Perhaps she has read about "the dangers" of vaccines in the first edition of Dr. Sears' The Vaccine Book . Or people on her Facebook page also say that the "preventable" diseases are just too rare anymore to ever take "the risk" of a vaccine with "known" risks. These vaccine risks are clearly explained, and even sometimes overstated (such as a risk of death for Haemophilus influenzae type B (HIB) vaccine) in the routinely distributed Centers for Disease Control and Prevention (CDC) Vaccine Information Sheet (VIS). On the other hand, the families typically overlook the risks of "omission, " or non-vaccination, such as brain damage or meningitis, etc., which are also clearly stated in the VIS.